An Examination Of Islamic Criminal Law And Positive Law In Relation To False Information In Gift Deeds (A Study Of Medan District Court Decision No. 737/Pid.B/2024) - Ardiansyah, Ardiansyah; Yazid, Imam (UNIVERSITAS PAKUAN, 2025)
This study examines the tindak pidana keterangan palsu in current affairs from the perspectives of positive and Islamic law, with a focus on Putusan Pengadilan Negeri Medan Nomor 737/Pid.B/2024. This is important because, as an otentik act, hibah has a high degree of purity, but rentan is used in conjunction with palsu keterangan that implies the kerugian of law and the public's lack of trust in the government. The study employs a normative legal approach that includes undang-undang, kasus, conceptual, and perbandingan analysis. According to the study's findings, hakim menerapkan Pasal 266 jo. Pasal 55 KUHP by promoting the use of niat (mens rea) and tindakan to fully encase the keterangan palsu (actus reus). From the perspective of jinayah fiqh, this perbuatan is related to syahādah az-zūr (kesaksian palsu), which includes large dosa and can be explained by sanksi ta'zir demi kemaslahatan. Comparative analysis highlights the similarities between Islamic and positive law, despite their differences in sanksi orientation: Islamic law emphasizes morality and substantiation, whereas positive law emphasizes adherence to the law. This study recommends strengthening notary integrity, raising the bar for active verification, and incorporating Islamic legal principles into positive legal practice to prevent corruption and improve legal performance.